Geometric Algorithms for Finding a Point in the Intersection of Balls - Lushchakova, I. N. (Automation and remote control, 2020)
We consider a problem of finding a point in the intersection of n balls in the Euclidean space E m . For the case m = 2 we suggest two algorithms of the complexity O ( n 2 log n ) and O ( n 3 ) operations, respectively. For the general case we suggest an exact polynomial recursive algorithm which uses the orthogonal transformation of the space E m .